Spheroidal nanoparticles as nanoantennas for fluorescence enhancement. (3rd August 2009) - Mohammadi, A.; Kaminski, F.; Sandoghdar, V.; Agio, M.
Nanoantennas made of spheroidal metal nanoparticles are studied as a function of several parameters, namely aspect ratio, volume, background index and metal. Single nanospheroids are analysed using the polarisability theory with radiative and depolarisation corrections, while double spheroids are investigated using the finite-difference time-domain method. We focus on the spectral position of the plasmon resonance and on the scattering efficiency for applications related to the fluorescence enhancement of emitters. We show that a careful choice of the parameters allows covering wavelengths ranging from the UV to the near IR spectrum, while keeping the scattering efficiency close to 100%. We also discuss the role of the optical constants in determining the nanoantenna performances.